STUDI PENERAPAN SISTEM MANAJEMEN KESEHATAN DAN KESELAMATAN KERJA (K3) PT.WASKITA KARYA (PERSERO) Tbk SENDAWAR-KUTAI BARAT - DARMADI, YOSEP (KURVA S JURNAL MAHASISWA, 2014)
Bridge The data needed rain fall data, data on land use and topographic dat. Rain falldata were analyzed data used is the maximum daily rainfall data pahoman station with other stations comparisons. Flooding is a state  of natural disaster phenomena which are related to the amount of damage in terms of life and material. Flooding began increasing population, climate change and land use change. capacity and the amount of sediment in the Bridge causing inundation / flooding. Other issues also arise from domestic Water. Dense urban areas can’t process individual waste water. So that, the will flow inti the urban bridge system.In this study , rain fall plays an important role in the evaluation and planningof urban intensity of rain isuseful to calculate the peak discharge by rational methods. Based on data, flood from The several channels at Sendawar Melak   as polres road, Simpang Busur  road, Muso Salim roadThe evaluation was done by analysis of the discharge of each drainage channel acrossthe. After an evaluation there are several drainage channelsneed to redesign like Kartini channel and Teuku Umar channel, and some drainagechannels need to be normalized as Melak ilir channel,and  Melak Kutai Barat Sendawar  channel.